2022
DOI: 10.1021/acsomega.2c05198
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Mechanism of Stereocomplexes and Homocrystals in High-Performance Symmetric and Asymmetric Poly(lactic acid) Enantiomers: Qualitative Methods

Abstract: To systematically explore the critical contributions of both molecular weights and crystallization temperature and chain length and molar ratios to the formation of stereocomplexes (SCs), our group quantitatively prepared a wide MW range of symmetric and asymmetric poly(lactic acid) (PLA) racemic blends, which contains L-MW PLLA with M n > 6k g/mol. The crystallinity and relative fraction of SCs increase with T c , and the SCs are exclusively formed at T c > 180 °C in M/H-MW racemic blends. When MWs of one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Additionally, the spatial heterogeneity and arrangement of PLLA and PDLA chains which has been displayed under the ''Effect of mixture mass ratios or molar ratios of PLA enantiomeric blends'' section in less-entangled blends also affect the formation of SC crystallization. 73 Besides the conventional melt blending, solution blending techniques, and supercritical fluid (SCF), newer techniques such as annealing, 20,21,45,46,62 electrospinning, 33,35,50,112 printing, 105 and templating 113 have been reported to prepare SCs between enantiomeric PLLA and PDLA chains. In another study, S. H. Im et al 111 introduced a new technique for SC crystallization using an oil-in-water (O/W) emulsion blending method.…”
Section: Processing Methods Of Plamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the spatial heterogeneity and arrangement of PLLA and PDLA chains which has been displayed under the ''Effect of mixture mass ratios or molar ratios of PLA enantiomeric blends'' section in less-entangled blends also affect the formation of SC crystallization. 73 Besides the conventional melt blending, solution blending techniques, and supercritical fluid (SCF), newer techniques such as annealing, 20,21,45,46,62 electrospinning, 33,35,50,112 printing, 105 and templating 113 have been reported to prepare SCs between enantiomeric PLLA and PDLA chains. In another study, S. H. Im et al 111 introduced a new technique for SC crystallization using an oil-in-water (O/W) emulsion blending method.…”
Section: Processing Methods Of Plamentioning
confidence: 99%
“…3. Guo et al 73 synthesized a wide molecular weight range of PLA enantiomers (6.7–210 kDa) and prepared different blending ratios of PLLA/PDLA racemic blends to confirm the existence of multi-complexation and attain exclusive SC crystallization (L: 6.7 kDa, D: 95 kDa) between the L/M-MW PDLA and H-MW PLLA chain. Notably, the PLA chains still have unavoidable entanglement due to the absence of ECC.…”
Section: Improved Sc Crystallization In the Enantiomeric Blends Of Pl...mentioning
confidence: 99%
“…4,10 It is well known that copolymers and blends are two common but effective approaches to enhancing the properties of the polymer matrix. 11,12 Therefore, PLA block copolymers have been widely concerned in recent years. 13 Such PLA block copolymers have been investigated, including PS/PLLA block copolymers, 14 PCL/PLLA block copolymers, [15][16][17][18][19] PEG/PLLA block copolymers, 17,[20][21][22][23] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 3 Synthesis of 5A-MPEG-b-PLLA-g-Glu (5A-MPELAG)(11), and 5A-Glu-g-PLLA-b-PEG-b-PLLA-g-Glu (5A-PELAG)(12).…”
mentioning
confidence: 99%
“…Since Y. Ikada proposed the stereocomplex (SC) crystallization of PLLA and PDLA in 1987, a large number of studies on the formation of the SC have been reported. The chemical and physical properties of SC PLA strongly exceed those of its parent enantiomeric pure, homocrystalline polymers, such as higher mechanical strength, better thermal stability, lower thermodegradation, etc. , For example, the blending of PLLA and PDLA can result in the formation of SCs with a melting point of about 50 °C higher than that of homocrystals (HCs). …”
Section: Introductionmentioning
confidence: 99%